Susceptibility of spring wheat cultivars and breeding lines to Septoria nodorum Berk. - Karjalainen, Reijo; Laitinen, Aino; Juuti, Tapio (Agricultural and Food Science, 1983)
Screening techniques for detecting the susceptibility of spring wheat cultivars and breeding lines to Septoria nodorum Berk. were studied in trials carried out in southern Finland. Small screening plots were artificially inoculated with the pathogen and subsequent observations showed that the early cultivars Apu, Ulla, Hja 21600 and the late cultivar Tähti were the most susceptible. The rank correlation between field assessments from naturally infected plots and assessment from artificially inoculated small screening plots was moderately high. The correlations between 1000 grain weight and disease severity were negatively significant in some susceptible cultivars, but also in some resistant cultivars A weak positive correlation between 1000 grain weight and disease severity was observed in some resistant and also in some susceptible varieties. Although our results do not show consistent trends we conclude that the use of small screening plots is an effective means of detecting differences in symptom expression among breeding lines and cultivars.